Precarization of Work and Migration: A Review of the International Literature - Matias, Guilherme Primo; Silva, Gabrielle Ribeiro Rodrigues da; Farago, Fabio Emanuel (Internext, 2020)
Objective: This research aims to highlight the relation between precarization of work and migration, based on the understanding that migrant workers take part assisting in the economic and social development of the countries. Method: The methodology used was a systematic review of the international literature on precarious work and migration in the period from 2008 to 2018. Main results: People migrate between countries for economic, social or political factors. Common of these three reasons is the desire to have a better life conditions. Even in some cases these migrants get access to benefits, they probably will suffer some kind of precariousness - whether in unhealthy services, without legal protection or living in unsuitable housing. This is the ambivalent nature of the precarious work – and its consequences. Relevance/originality: It is observed that large part of the research on migration in the least developed countries began with propositions borrowed from researchers who codified the experience of developed countries. It is necessary in our field to present a systematic examination of how precarization and migration are addressed in the organizational studies. Theoretical/Methodological Contributions: As a contribution to the field, in this paper it is proposed a theoretical model that involves the two phenomena and, provides the reader with standardized and systematic scientific information that may assist in the development of the field by mapping existing knowledge on this subject.